UPAYA REHABILITASI EKOSISTEM TERUMBU KARANG TERDAMPAK TUMPAHAN MINYAK DI DESA FAEKHUNA, KECAMATAN AFULU, KABUPATEN NIAS UTARA - Hilal Idama Dalimunthe; Hasbi Husaini; Vindy Rilani Manurung; Muhammad Azis Yudhiwinata; Machmul Prayudi Harahap; Muhammad Adam Pahlevy; Muhammad Najhan Adisusilo; Muhammad Fahmi Abdillah; Abdullah Hanif; Stefany Florencia; Hana Sazida; Daniel Tambunan; Muhammad Thariq Abshar; Ferdiansyah Manurung; Bina Kristian Waruwu (Jurnal Abdi Insani, 2023)
Faekhuna'a Village is one of the villages affected by asphalt oil spills. The oil spillage that has polluted the waters has led to a decline in the income of fishermen, due to the damage to coral reefs. To address this problem, direct implementation of the "one house, one coral transplantation" initiative using science and technology (IPTEK) can help mitigate the issues. The objective is to address the problem of asphalt oil spills through the application of IPTEK, optimize the role of the community, educate the community, and create a mindset among the community regarding the importance of environmental factors in the local economy. The method conducted by outreach and simulation. The stages are preparation, participation in the activities by the Faekhuna'a Village officials, 15 members of fisherman group (KUB), PPK 15 students of ORMAWA team and one supervising lecturer, lecturers and students from the University of North Sumatra's Off-Campus Study Program (PSDKU) in North Nias, and support from National Search and Rescue Agency (BASARNAS) of North Nias Regency. Through the program, providing education and awareness about the ecological aspects of life. The application of science and technology (IPTEK) has been warmly received by the community, who have actively contributed to ecosystem restoration through the PPK ORMAWA program. The fishermen has been educated about the crucial role of the coral reef ecosystem in improving the livelihoods. The use of IPTEK, specifically coral transplantation, has proven to be a viable, efficient, complex, adaptable, and compatible approach that is easily implementable.